Sheathing-fastener connection strength based design method for sheathed CFS point-symmetric wall frame studs. (October 2021) - Selvaraj, Sivaganesh; Madhavan, Mahendrakumar; Lau, Hieng Ho
Abstract: Cold-formed steel (CFS) in construction delivers cost effectiveness and design flexibility. The instability failures of CFS Structural members significantly influences the failures of sheathing boards attached as an external cover. Therefore, present study experimentally examines the structural behavior of sheathing fastener connection in cold-formed steel wall frame. As a first attempt, strength and stiffness of the sheathing fastener connection is determined against the failure modes of point symmetric CFS wall frame studs. A new test setup has been developed to investigate the individual sheathing fastener failure modes. Parameters investigated include sheathing board types (varying thickness) and different dimensions of point-symmetric CFS studs. A total of forty-one individual fastener connection tests were carried out. The experimental investigation revealed that the fastener connection strength varies depending on the geometric dimensions of CFS stud and material composition of sheathing board. The result indicated that the bracing effect provided by plain gypsum board (fiber less) is insignificant and should not be considered for design. For sheathing boards with fiber composition, a generic parameter [ratio to design moment (Mx or My ) to CFS stud depth ( h )] is introduced to consider the structural bracing effect in CFS wall panel design. The limitations to consider the bracing effect of sheathing in the design of CFS wall frame studs are suggested for minor axis buckling and major axis buckling.